The History of the Protojournalism of Ancient Civilizations. Part 2. The Types of Communications of the Hellenistic States and Ancient Roma - Larisa Vladimirovna Lytkina (Управленческое консультирование, 2018)
In the article, the main spaces of communication of the Hellenistic states and Ancient Rome are investigated. Emergence of a gloss as independent genre is proved, the epistolography role in formation of protojournalistic work is established, stages of formation of ancient Roman newspapers are traced, their formats are defined, and the media text “The first speech against Lucius Sergius Catilina” of Marcus Tulius Cicero is analyzed. Types of communicative tactics and strategy of the Hellenistic period and era of Ancient Rome in the Russian historiography still did not become a subject of special scientific research. Therefore, the address of the author, first, to reanimation and an assessment of the essay of the French scientist G. Boissier of “Newspapers of Ancient Rome” (1895), secondly, to the analysis of media texts of the studied period is submitted reasonable. In the article, the typological model reflecting both genesis and ways of evolution the protojournalistic types of communication of ancient civilizations is built; the technique of the analysis of the media ancient Roman text is offered.